AN ANALYSIS ON LEXICAL ASPECTS IN CARTOON DISCOURSES IN “DONALD DUCK” (A COMIC BOOK PUBLISHED BY M & C PT. GRAMEDIA MAGAZINE) - Onisimus Faot; Ivona Dorobia; Paskalis Kaipman (Bajang Institute, 2025)
This paper presents an analysis on lexical aspect in cartoon discourses in “donald duck” (a comic book published by m & c pt. gramedia megazine). Through this writing, the writer would like to conduct a research about what are lexical aspects in cartoon discourses in Donald Duck?. The aim of this study is to find out the lexical aspects in cartoon discourses in Donald Duck. The method in research is a descriptive qualitative method by doing a library research. The subject of this research was taken to be analyzed in this writing is the English –Indonesia languages cartoon discourses especially in Donald Duck Book in the written form. The writer analyzed lexical aspects in cartoon discourses mentioned by Vendler (1967:151) they are: (a) a state verb (e.g., love), (b) an activity verb (e.g., call), (c) an accomplishment verb (e.g., build a zoo), (d) an achievement verb (e.g., fall). Cartoonists should have their own lexical aspect. In order to differentiate from another kinds of discourses. In creating cartoon discourses, not all the lexical aspects used once in a cartoon but it depends on the story and needs in cartoon itself. The writer suggests to those whoever interest in the field of cartoon discourses should master the lexical aspects of cartoon discourses because lexical aspects is a basic in creating cartoon discourse, oral or written form